Metabolic syndrome and calcium: the effects on body composition and biochemical parameters among premenopausal women - Arıtıcı, Gözde; Bas, Murat (Progress in Nutrition, 2018)
Aims: The objective of this study is to investigate the association of the dietary calcium intake with the risk of metabolic syndrome among the premenopausal women. Methods: The cross-sectional study was conducted between August and December 2015. One hundred and forty-six premenopausal women, from 19 to 52 years old, participated in the study. The diet section of this study was based on the 3-day self-reported nutrient intake of the recipients. All participants agreed to participate and be submitted to clinical, dietary, anthropometric and biochemical evaluations at the Endocrinology Department at Baskent University Hospital in Ankara. Multiple logistic regression models were used to estimate multivariable odds ratios (ORs) and 95% CIs comparing different dietary intake levels of calcium. Results: Participants in ‘the group without metabolic syndrome’ exhibited significantly higher BMI, waist circumferences, body fat and visceral fat (p<0.001) when they were compared with the group with metabolic syndrome. Systolic blood pressure, diastolic blood pressure, low density lipoprotein-cholesterol and triglyceride level were higher in the group with metabolic syndrome than the group without metabolic syndrome (p<0.001). Compared to women without metabolic syndrome, women with metabolic syndrome had lower serum calcium level and dietary calcium intake (p<0.001). In multiple logistic regression analysis, serum calcium level within normal range was positively associated with the risk of having metabolic syndrome (odds ratio 2.59, 95% confidence interval 0.59-1.51). Conclusions: This study suggests that high dietary calcium intake and high serum calcium level are associated with a decreased risk of metabolic syndrome among Turkish premenopausal women. These findings may lead to an effective approach to the reduction of the risk of metabolic syndrome by means of dietary therapy and especially by means of the consumption of dairy products.